2008
DOI: 10.1136/pgmj.2007.065540
|View full text |Cite
|
Sign up to set email alerts
|

Massive cardiac invasion by amelanotic melanoma with obstructive clinical features

Abstract: Reports of malignant melanoma involving the heart usually describe metastatic spread of pigmented (melanotic) forms of this tumour. We describe, and illustrate, a patient presenting with features related to cardiac tamponade and intracardiac obstruction. Transthoracic echocardiography initially showed a large mass within the right ventricular outflow tract. The full extent of infiltration of this tumour was demonstrated by computed tomography scanning and the specific tumour type by immunohistochemical stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…A comprehensive literature review identified only 3 published case reports of amelanotic melanoma metastasizing to the heart: 2 cases with evidence of right atrial metastasis and the third with metastasis involving the atrioventricular groove ( 1 , 2 , 3 ). To our knowledge, this is the first reported case of amelanotic melanoma with left ventricular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature review identified only 3 published case reports of amelanotic melanoma metastasizing to the heart: 2 cases with evidence of right atrial metastasis and the third with metastasis involving the atrioventricular groove ( 1 , 2 , 3 ). To our knowledge, this is the first reported case of amelanotic melanoma with left ventricular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostisch richtungweisend war der immunhistochemische Nachweis der Expression von HMB-45, Melan-A/MART-1 und S100 im Melanom, jedoch nicht im Nierenzellkarzinom. Die Kombination dieser Marker wird als Standard für die Melanomdiagnostik angesehen, und ist selbst in der Mehrzahl der amelanotischen Melanome positiv [4,5]. Melan-A/MART-1 ist hierbei der sensitivere, HMB45 der spezifischere Marker.…”
unclassified